Is Marital Status a Critical Contingency in the Relationship Between Physical Limitations and Subjective Well-Being Among Japanese Adults?. (December 2014) - Bierman, Alex
Research demonstrates that physical limitations are related to lower levels of subjective well-being, but little research has examined whether marital status modifies this relationship, despite evidence showing that marital status is a substantial determinant of subjective well-being. Marital status is likely to be an especially important contingency in collectivistic cultures such as Japan, because cultural emphases heighten the importance of the marital partner as a resource when married individuals experience physical limitations. The current research uses a probability sample of Japanese adults to show that physical limitations are negatively related to both life satisfaction and happiness only among the nonmarried. Marriage obviates the association between limitations and subjective well-being by preventing losses in a sense of control. Furthermore, the married are protected regardless of the level of spousal support or strain, suggesting that the social integration function of marriage is pivotal in the creation of these protective effects.